Spt6 Is Essential for rRNA Synthesis by RNA Polymerase I - Engel, Krysta L. (Mol Cell Biol, 2015)
Spt6 (suppressor of Ty6) has many roles in transcription initiation and elongation by RNA polymerase (Pol) II. These effects are mediated through interactions with histones, transcription factors, and the RNA polymerase. Two lines of evidence suggest that Spt6 also plays a role in rRNA synthesis. First, Spt6 physically associates with a Pol I subunit (Rpa43). Second, Spt6 interacts physically and genetically with Spt4/5, which directly affects Pol I transcription. Utilizing a temperature-sensitive allele, spt6-1004, we show that Spt6 is essential for Pol I occupancy of the ribosomal DNA (rDNA) and rRNA synthesis. Our data demonstrate that protein levels of an essential Pol I initiation factor, Rrn3, are reduced when Spt6 is inactivated, leading to low levels of Pol I-Rrn3 complex. Overexpression of RRN3 rescues Pol I-Rrn3 complex formation; however, rRNA synthesis is not restored. These data suggest that Spt6 is involved in either recruiting the Pol I-Rrn3 complex to the rDNA or stabilizing the preinitiation complex. The findings presented here identify an unexpected, essential role for Spt6 in synthesis of rRNA.